1981
DOI: 10.1126/science.213.4511.1005
|View full text |Cite
|
Sign up to set email alerts
|

Trace Water Content of Salt in Louisiana Salt Domes

Abstract: The trace water content of salt in six Louisiana salt domes has been determined and has been found to be the lowest of any terrestrial rock type. The average water content of normal domal salt is on the order of 0.003 percent by weight, but anomalous zones within salt stocks can have more than ten times this amount. From the average value, the minimum amount of water in liters, W, available to collect around a radioactive waste repository is given as W = 0.28 r(3), where r is the radius in meters of the sphere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Samples of chev ron or cumulate halite with primary fluid inclusions were selected for analysis based on petrographic examination of small cleavage fragments. A modification of the vacuum vola tilization method of Knauth and Kumar (1981) and Knauth and Beeunas (1986) was used to release the fluid inclusion Table 1…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Samples of chev ron or cumulate halite with primary fluid inclusions were selected for analysis based on petrographic examination of small cleavage fragments. A modification of the vacuum vola tilization method of Knauth and Kumar (1981) and Knauth and Beeunas (1986) was used to release the fluid inclusion Table 1…”
Section: Methods and Resultsmentioning
confidence: 99%
“…According to Knauth and Kumar (1981) and Roedder and Bassett (1981), the adsorbed water on the surface of halite samples can be removed by submitting the sample to a high vacuum at 23 35°C for 30 minutes or longer. However, clay and some other hydrous minerals which are considered to exist in natural halite samples will dehydrate slowly above 100°C.…”
Section: Methodsmentioning
confidence: 99%
“…Roedder and Belkin (1979) found that many inclusions (< 100 µm) did not decrepitate even at 250°C when the heating rate was sufficiently low. Knauth and Kumar (1981) reported that the water, which they considered to have been derived from fluid inclusions, started to outgas at 280°C in a vacuum. Based on the above information, the preheating temperature was set at 130 --150°C to expel adsorbed atmospheric moisture and gases as well as trapped water and gases in fine cracks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that salt domes contain less intergranular and inclusional fluid because of textural changes during stress deformation, but they may contain more water in hydrated minerals. This appears to vary with site history and mineralogy, such that site-specific testing is warranted (Knauth and Kumar, 1981;De Las Cuevas and Pueyo, 1995).…”
Section: Repository Construction and Operation • Excavationmentioning
confidence: 99%